If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 360 = x + (9x + -35) + (x + -46) + 0.5x Reorder the terms: 360 = x + (-35 + 9x) + (x + -46) + 0.5x Remove parenthesis around (-35 + 9x) 360 = x + -35 + 9x + (x + -46) + 0.5x Reorder the terms: 360 = x + -35 + 9x + (-46 + x) + 0.5x Remove parenthesis around (-46 + x) 360 = x + -35 + 9x + -46 + x + 0.5x Reorder the terms: 360 = -35 + -46 + x + 9x + x + 0.5x Combine like terms: -35 + -46 = -81 360 = -81 + x + 9x + x + 0.5x Combine like terms: x + 9x = 10x 360 = -81 + 10x + x + 0.5x Combine like terms: 10x + x = 11x 360 = -81 + 11x + 0.5x Combine like terms: 11x + 0.5x = 11.5x 360 = -81 + 11.5x Solving 360 = -81 + 11.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11.5x' to each side of the equation. 360 + -11.5x = -81 + 11.5x + -11.5x Combine like terms: 11.5x + -11.5x = 0.0 360 + -11.5x = -81 + 0.0 360 + -11.5x = -81 Add '-360' to each side of the equation. 360 + -360 + -11.5x = -81 + -360 Combine like terms: 360 + -360 = 0 0 + -11.5x = -81 + -360 -11.5x = -81 + -360 Combine like terms: -81 + -360 = -441 -11.5x = -441 Divide each side by '-11.5'. x = 38.34782609 Simplifying x = 38.34782609
| 2x-19=(-5)x+9 | | 2u-11=5(u+2) | | x-7=4x+1 | | 8x+18=3x+-7 | | 6x+1=4x-13 | | (x-15)-(2x-13)=1 | | 6x(6x)+5(3x(3x)-x)-3x= | | 4x-3+90=180 | | f(x)=500-75x | | 3x(x-2)=24 | | 3x(x-2)=23 | | (1+0.05)4= | | A=0.5(b+12)5 | | 2x-6+2x-9=180 | | 9+x+7+x=50 | | 2-3(x-5)=20 | | 23x=10x+5 | | 4-y=230 | | 4x=18+4 | | 10x=5x+2 | | 5(3)=3645 | | (11x*2/3)*(11x*-2/3) | | 19-a=-2a | | 2x-27=95 | | 10-6x=20-26x | | 3x^2-4x+119=0 | | 70-2x=85-3x | | 4/d=12 | | y^2-8y+154=0 | | 4x-32=3x+10 | | -0.33-m=-0.11m+0.037-0.33m | | -40=(x-10) |